Evalusation of Chemical Amendments for Effective Reclamation of Saline-Sodic and Smile Soils - Misra, S.G.; Khan, T. (Journal of Soil and Water Conservation, 2022)
Many such saline sodic soils may be encountered under the field conditions which in view of the undesirable anionic and cationic composition as well as unsuitable quality of ground waters, cannot be improved by merely leaching them or adding organic materials. Rather such treatments may deteriorate the soils further. In such soils, whenever a rapid and effective reclamation is desired, the use of chemical amendments is the only attractive and feasible alternative.